Clinical trial budgeting approaches in Switzerland—a meta-research study - Alexandra Griessbach; Malena Chiaborelli; Klaus Ehrlich; Regina Grossmann; María De Medina Redondo; Aurélie Fayet; Reinhard Maier; Sven Trelle; Angèle Gayet-Ageron; Alessandro Ceschi; Benjamin Speich; Matthias Briel; et al. (Trials)
Abstract Background Conducting clinical trials is resource demanding. Mirroring challenges experienced elsewhere, clinical trials conducted in Switzerland often face overoptimistic budget estimations and insufficient funding, leading to trial discontinuation and research waste. As a first step to address this problem, we investigated the current approaches to estimate clinical trial budgets in Switzerland. Methods We collected and examined the budgeting tools and approaches for clinical trials provided by the seven Swiss clinical trial units (CTUs) and the Swiss National Science Foundation (SNSF). We compared available approaches to the publicly accessible budgeting tool of the Belgian Health Care Knowledge Centre (KCE). For each approach, we collected data about user-testing, the availability of prespecified cost items, and estimates on cost ranges. Results We found substantial heterogeneity in budget calculation approaches used by Swiss CTUs. None of the currently used tools and approaches provided by the seven CTUs or the SNSF was user-tested and neither supplied cost ranges for investigators to rely on. Five CTU tools included a detailed list of cost items. The SNSF provided a costing template with broad categories and is available for open grant applications only. One CTU tool was publicly available. The publicly available Belgian KCE tool was developed with user feedback and provided a detailed list of cost items, some cost ranges, and an instruction manual. Conclusion Stakeholders should consider improving budgeting practices in Switzerland by standardizing cost items and user-testing approaches. The continuously improved Belgian KCE tool could provide orientation.